2008
DOI: 10.1038/nature06720
|View full text |Cite
|
Sign up to set email alerts
|

CO2 regulator SLAC1 and its homologues are essential for anion homeostasis in plant cells

Abstract: The continuing rise in atmospheric [CO2] is predicted to have diverse and dramatic effects on the productivity of agriculture, plant ecosystems and gas exchange. Stomatal pores in the epidermis provide gates for the exchange of CO2 and water between plants and the atmosphere, processes vital to plant life. Increased [CO2] has been shown to enhance anion channel activity proposed to mediate efflux of osmoregulatory anions (Cl- and malate(2-)) from guard cells during stomatal closure. However, the genes encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
711
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 557 publications
(743 citation statements)
references
References 30 publications
21
711
0
7
Order By: Relevance
“…The NtrbohD protein, 28 G protein-coupled receptors (GPCRs), 29 fast vacuolar (FV) channels, K + -selective vacuolar (VK) cation channels, 30 slow vacuolar (SV) channels, slow anion channel-associated 1 (SLAC1) 31,32 and H + -ATPases (AHA1 and AHA2) 33 are localized to the membrane and function during abiotic or biotic responses in guard cells. 34 These findings also demonstrate that the guard cell signal transduction in response to biotic and abiotic signals shares some common steps, including NO accumulation in guard cells.…”
Section: Role Of Vpe In Stomatal Movementmentioning
confidence: 99%
“…The NtrbohD protein, 28 G protein-coupled receptors (GPCRs), 29 fast vacuolar (FV) channels, K + -selective vacuolar (VK) cation channels, 30 slow vacuolar (SV) channels, slow anion channel-associated 1 (SLAC1) 31,32 and H + -ATPases (AHA1 and AHA2) 33 are localized to the membrane and function during abiotic or biotic responses in guard cells. 34 These findings also demonstrate that the guard cell signal transduction in response to biotic and abiotic signals shares some common steps, including NO accumulation in guard cells.…”
Section: Role Of Vpe In Stomatal Movementmentioning
confidence: 99%
“…Elevated CO 2 concentration activates anion channels, resulting in depolarization of plasma membrane in guard cells, causing efflux of solutes and stomatal closure [7][8][9][10] . Earlier studies in Arabidopsis identified several mutants with defects in CO 2 -induced stomatal movements [11][12][13][14][15][16][17][18][19] . However, most of these mutants including abi1-1, abi2-1, gca2, ost1 and slac1 were insensitive to both CO 2 and abscisic acid (ABA), representing components shared by both signalling pathways 5,20 .…”
mentioning
confidence: 99%
“…Activation of the slow (S-type) anion channels for anion efflux has been regarded as a critical step in stomatal closure 18,[21][22][23][24] . SLAC1 (Slow Anion ChannelAssociated 1) is a component of the S-type anion channel in Arabidopsis guard cells 14,15 . When expressed in Xenopus oocytes, SLAC1 forms a channel that is permeable to Cl À and NO 3 À , but not to HCO 3 À 23, 24 .…”
mentioning
confidence: 99%
“…Recent molecular and electrophysiological studies showed that Arabidopsis SLAC1 is required for anion channel activity in the PM of guard cells and is more permeable to Cl − than malate [5], indicating that SLAC1 functions as a slow-type (S-type) anion channel located at the PM in plant cells. This channel, activated by the stress hormone abscisic acid (ABA), ozone, and CO 2 , is involved in the early steps leading to the volume regulation of guard cells and stomatal closure [810]. Four orthologs of SLAC1, SLAH1-4 have been identified in Arabidopsis and constitute the SLAC/SLAH family [8].…”
mentioning
confidence: 99%
“…This channel, activated by the stress hormone abscisic acid (ABA), ozone, and CO 2 , is involved in the early steps leading to the volume regulation of guard cells and stomatal closure [810]. Four orthologs of SLAC1, SLAH1-4 have been identified in Arabidopsis and constitute the SLAC/SLAH family [8]. However, the physiological roles of SLAC/SLAH family proteins in plant immunity have not yet been elucidated.…”
mentioning
confidence: 99%